Students’ Perceptions in English Teachers’ Interaction Patterns of the Second Grade SMP N 17 Batanghari University Academic Year2016/2017 - Nina Utami; Wennyta Wennyta; Khidayatul Munawwaroh (Universitas Batanghari Jambi, 2017)
AbstractThe purpose of this study is to find out the students' perceptions in English teachers' interaction patterns in the learning process at SMP N 17 Batanghari. The method used in this research isdescriptive with qualitative approach. The data of this study is collect by using observation and interview. This study involved 45 students of second grade at SMP N 17 Batanghari academic year 2016/2017 as the subject of the study. The researcher found that 24 students (53%) said that their teacher used one-way pattern or lecture method, 13 students (29%) said two-way pattern or asking and answering method and 8 students (18%) said three-way or multi-way or discussion. From the findings, it isshow that students' perceptions in English teachers' interaction patterns are very various. They have their own opinion and it is strong reasons. It can concluded that in second grade SMP N 17 Batanghari more dominant use one-way interaction pattern (53%), although sometimes interspersed with other patterns. Basically, the teacher can apply variations of any patterns that feel appropriate in the process of learning to teach English. So, students who are taught do not feel bored to learn with the same patterns and methods every time.Keywords: Students’ perceptions, Teachers’ interaction patterns